Cytomegalovirus Generates Assembly Compartment in the Early Phase of Infection by Perturbation of Host-Cell Factors Recruitment at the Early Endosome/Endosomal Recycling Compartment/Trans-Golgi Interface - Lučin, Pero; Jug Vučko, Natalia; Karleuša, Ljerka; Mahmutefendić Lučin, Hana; Blagojević Zagorac, Gordana; Lisnić, Berislav; Pavišić, Valentino; Marcelić, Marina; Grabušić, Kristina; Brizić, Ilija; Lukanović Jurić, Silvija (Frontiers in Cell and Developmental Biology, 2020)
Beta-herpesviruses develop a unique structure within the infected cell known as an assembly compartment (AC). This structure, as large as the nucleus, is composed of host-cell-derived membranous elements. The biogenesis of the AC and its contribution to the final stages of beta-herpesvirus assembly is still unclear. In this study, we performed a spatial and temporal analysis of the AC in cells infected with murine CMV (MCMV), a member of the beta-herpesvirus family, using a panel of markers that characterize membranous organelle system. Out of 64 markers that were analyzed, 52 were cytosolic proteins that are recruited to membranes as components of membrane-shaping regulatory cascades. The analysis demonstrates that MCMV infection extensively reorganizes interface between early endosomes (EE), endosomal recycling compartment (ERC), and the trans-Golgi network (TGN), resulting in expansion of various EE-ERC-TGN intermediates that fill the broad area of the inner AC. These intermediates are displayed as over-recruitment of host-cell factors that control membrane flow at the EE-ERC-TGN interface. Most of the reorganization is accomplished in the early (E) phase of infection, indicating that the AC biogenesis is controlled by MCMV early genes. Although it is known that CMV infection affects the expression of a large number of host-cell factors that control membranous system, analysis of the host-cell transcriptome and protein expression in the E phase of infection demonstrated no sufficiently significant alteration in expression levels of analyzed markers. Thus, our study demonstrates that MCMV-encoded early phase function targets recruitment cascades of host cell-factors that control membranous flow at the EE-ERC-TGN interface in order to initiate the development of the AC.